POTENSI PEMBANGKIT LISTRIK TENAGA ANGIN SEBAGAI ALTERNATIF PENERANGAN JALAN DI PANTAI BAMBANG KABUPATEN LUMAJANG - Putri Wihatma Andianti; Yushardi (UHN IGB Sugriwa Denpasar, 2022)
Bambang Beach is one of the water tourism located in Lumajang Regency. This beach is located about 24 km from the center of Lumajang City. Bambang Beach is included in the South Beach which has big waves and winds. Bambang Beach is no longer visited by tourists because the beach conditions are not clean and the waves are high. In addition, the access road to the beach is very quiet and minimally lit at night. The purpose of this article is to find out the potential for wind at Bambang Beach, Lumajang Regency as a Wind Power Plant (PLTA) as an alternative for street lighting and also to re-evaluate the benefits of Bambang Beach for the surrounding community. The research method used in this article is a literature study, by utilizing the facts or wind data in Indonesia and in Lumajang Regency. Several studies from the journal literature explain that wind can be used as an effective source of electrical energy. However, the data and facts that occurred at Bambang Beach are not very suitable to be used as a Wind Power Plant. Thus, the solution that can be used so that Bambang Beach can benefit the surrounding community is to clean and maintain the beach environment so that it is crowded with tourists, so that it can increase the income of the local community. With the return of the bustle of tourists, it can be used as income and the funds obtained can be used to make lighting along the road to Bambang Beach